The allosteric inhibition of glycine transporter 2 by bioactive lipid analgesics is controlled by penetration into a deep lipid cavity - Wilson, Katie A. (J Biol Chem, 2021)
The role of lipids in modulating membrane protein function is an emerging and rapidly growing area of research. The rational design of lipids that target membrane proteins for the treatment of pathological conditions is a novel extension in this field and provides a step forward in our understanding of membrane transporters. Bioactive lipids show considerable promise as analgesics for the treatment of chronic pain and bind to a high-affinity allosteric-binding site on the human glycine transporter 2 (GlyT2 or SLC6A5). Here, we use a combination of medicinal chemistry, electrophysiology, and computational modeling to develop a rational structure–activity relationship for lipid inhibitors and demonstrate the key role of the lipid tail interactions for GlyT2 inhibition. Specifically, we examine how lipid inhibitor head group stereochemistry, tail length, and double-bond position promote enhanced inhibition. Overall, the l-stereoisomer is generally a better inhibitor than the d-stereoisomer, longer tail length correlates with greater potency, and the position of the double bond influences the activity of the inhibitor. We propose that the binding of the lipid inhibitor deep into the allosteric-binding pocket is critical for inhibition. Furthermore, this provides insight into the mechanism of inhibition of GlyT2 and highlights how lipids can modulate the activity of membrane proteins by binding to cavities between helices. The principles identified in this work have broader implications for the development of a larger class of compounds that could target SLC6 transporters for disease treatment.